STUDY OF THE MICROFLORA AND PH OF THE SKIN ENVIRONMENT IN PATIENTS WITH ZOOANTHROPONOTIC TRICHOPHYTOSIS OF THE PUBIC REGION - U. B. Nurmatov dotsen; N.F. Nurmatova dotsent; I.B. Nurmatova dotsent; B. S. Azizov dotsent; U.A. Tashkenbaeva dotsent; S. S. Agzamkhodjaeva dotsent; Sh.T. Ayupova assistant (Scholar Express Journals, 2024)
The article describes the Study of the microflora and pH of the skin environment in patients with zooanthroponotic trichophytosis.
Keywords: Zoo anthroponotic; trichophytes and features; microbiology